2021
DOI: 10.1186/s13007-021-00734-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of spectroscopically determined leaf nutrition related traits and breeding selection in Sassafras tzumu

Abstract: Background Plant traits related to nutrition have an influential role in tree growth, tree production and nutrient cycling. Therefore, the breeding program should consider the genetics of the traits. However, the measurement methods could seriously affect the progress of breeding selection program. In this study, we tested the ability of spectroscopy to quantify the specific leaf nutrition traits including anthocyanins (ANTH), flavonoids (FLAV) and nitrogen balance index (NBI), and estimated th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Recent research has shown that variable selection of the original spectrum can reduce computational complexity and improve the predictiveness of the model (Alizadeh et al, 2019). In this study, Backward Variable Elimination (bve) (Eason, 1990;Austin, 2008), regularization elimination (rep) (Molajou et al, 2021), and significant multivariate correlation (sMC) algorithm (Liu et al, 2021) were used for variable selection.…”
Section: Spectral Pre-processing and Selection Of Characteristic Wave...mentioning
confidence: 99%
“…Recent research has shown that variable selection of the original spectrum can reduce computational complexity and improve the predictiveness of the model (Alizadeh et al, 2019). In this study, Backward Variable Elimination (bve) (Eason, 1990;Austin, 2008), regularization elimination (rep) (Molajou et al, 2021), and significant multivariate correlation (sMC) algorithm (Liu et al, 2021) were used for variable selection.…”
Section: Spectral Pre-processing and Selection Of Characteristic Wave...mentioning
confidence: 99%
“…The outcomes demonstrated that precipitation of driest month, precipitation of wettest month, temperature seasonality, and mean temperature of wettest quarter chiefly influenced the distribution. Furthermore, a comparison between the simulated outcomes of the distribution range during distinct periods revealed that the suitable habitat for S. tzumu contracted and shifted from the southern to the northern regions [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes demonstrated that precipitation during the driest quarter, precipitation during the wettest month, temperature seasonality, and mean temperature during the wettest quarter chie y in uenced the distribution. Furthermore, a comparison between the simulated outcomes of the distribution range during distinct periods revealed that the suitable habitat for S. tzumu contracted and shifted from the southern to the northern regions [17]. Genotyping-by-sequence (GBS) technology represented one of the streamlined genome sequencing methodologies, aiming to reduce genome complexity through the application of restriction enzymes and the incorporation of single nucleotide polymorphisms (SNPs) [18].…”
Section: Introductionmentioning
confidence: 99%